Increasing the occupational health and safety level by using specialized software - Morar Marius Simion; Păsculescu Vlad Mihai; Cioară Cristian Raul; Băbuţ Andrada Denisa (MATEC Web of Conferences, 2020)
Worldwide, but also at European Union level, the mining industry is subject to legislative and technical restrictions. For mining coal from underground is used a complex network of horizontal, vertical and inclined mine workings aiming at transporting and exhausting coal at the surface. In every mine unit, very important is the ventilation network, used for ensuring the oxygen for workers, for diluting explosive and/or toxic gases and for exhausting heat and humidity form the underground. Coal mining involves the risk of spontaneous combustion which, besides methane accumulations and improper ventilation, represents the main source generating work accidents, sometimes resulting in human losses. The current article proposes an analysis of the potentially explosive and/or toxic atmosphere for a longwall with undermined coal bed and of the use of specialized software for increasing the underground safety level by mining ventilation improvement.